Stock Market as the Main Segment of Capital Market - Farkhod Tursunbaevich, Mukhamedov; Abror Akhrorovich, Ibodullaev; Khabibullokh Ravshanugli, Razzokov (International Journal of Psychosocial Rehabilitation, 2020)
The article covers the full use of the financial and banking system, including the capital market, to improve the competitiveness of the national economy and the modernization of the economy and to bring this system to a new level.